Article processing charges and the stratification of open access publishing (PUBMET, 2022)
The Open Access movement promised to increase knowledge sharing within and beyond academia, sidestepping issues of structural inequality. In spite of this initial hope, emerging evidence shows that the model of author facing charges is erecting a new barrier, threatening equity in who can contribute to the scientific record. This talk will investigate the role of institutional resources in shaping publication outcomes across fields and countries and discuss wider implications of current threats to an equitable implementation of open research.